Corpus-driven Bantu Lexicography Part 2: Lemmatisation and Rulers for Lusoga - de Schryver, Gilles-Maurice; Nabirye, Minah (Lexikos, 2018)
This article is the second in a trilogy that deals with corpus-driven Bantu lexicography, which is illustrated for Lusoga. The focus here is on the macrostructure and in particular on the building of a lemmatised frequency list directly within a dictionary-writing system. The programming code for the parts of the lemmatisation that may be automated is included as addenda. A second focus is on the embedded part-of-speech and alphabetical rulers, for which it is shown how these may be used to plan the actual compilation of the dictionary entries.